2022
DOI: 10.3390/ijerph19137641
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Specific Servant Leadership and Employees’ Energy-Specific Pro-Environmental Behavior: Evidence from Healthcare Sector of a Developing Economy

Abstract: Environmental issues are significantly rising worldwide. Addressing the environmental issues and preserving the biosphere is a critical matter of concern in this era. The sheer amount of total greenhouse gas (GHG) emissions in the world is related to the energy sector, especially electrical energy. A bulk of electrical energy is consumed by individuals in buildings for cooling and heating purposes. Prior researchers have emphasized employing clean and green energy sources to deal with environmental issues. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 84 publications
5
34
0
1
Order By: Relevance
“…All this process encourages them to adopt a sustainable behavior toward energy saving and consumption. This finding is in line with the findings of some recent researchers who argued that different organizational factors like leadership and CSR could motivate employees to act pro-socially, especially from an energy perspective (Peng et al, 2022;Xu et al, 2022a). Especially in a recent study Xu et al (2022b) mentioned that the CSR and leadership style of a hotel organization significantly predicted ERPEB.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All this process encourages them to adopt a sustainable behavior toward energy saving and consumption. This finding is in line with the findings of some recent researchers who argued that different organizational factors like leadership and CSR could motivate employees to act pro-socially, especially from an energy perspective (Peng et al, 2022;Xu et al, 2022a). Especially in a recent study Xu et al (2022b) mentioned that the CSR and leadership style of a hotel organization significantly predicted ERPEB.…”
Section: Discussionsupporting
confidence: 91%
“…We feel that advancing the debate on the energy-saving behavior of an individual is important, at least for two reasons. First, the available literature indicates that individuals have a critical role in the decarbonization of a society (Ivanova et al, 2016;Peng et al, 2022); therefore, it is worthwhile to investigate major factors that can promote the energy-saving behavior of the individuals. Second, from the perspective of electricity consumption, the environmental data suggest that most of the electrical energy in buildings has been consumed by individuals for cooling or heating purpose (Energy, 2015;Arif et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that all CVs and CRs were significant because the average variance extracted (AVE) for all variables was above the cut-off value of 0.5 (establishing CV), and CRs were above 0.7 in all cases. This is in line with previous researchers [ 131 , 141 , 142 ].…”
Section: Methodssupporting
confidence: 94%
“…This questionnaire was adapted from different sources for which detailed information is provided in the subsequent paragraphs. Indeed, the initial questionnaire version was presented to the experts [ 129 , 130 , 131 , 132 ]. The outlay of the questionnaire was comprised of three sections.…”
Section: Methodsmentioning
confidence: 99%
“…In response to market and societal demands, initiatives to promote PEBs have increased within organizations [ 27 , 28 ]. Individuals vary in the extent to which they perceive and value CSR activities but working for organizations committed to environmental causes has a positive effect on work PEBs [ 21 , 29 ].…”
Section: Research Background and Hypotheses Developmentmentioning
confidence: 99%